Randomised observer blind comparative trial of ceftriaxone and penicillin in treating uncomplicated gonorrhoea in men and women. - Dixon, C A (1986)
Ceftriaxone is a third generation cephalosporin with a prolonged half life. It was used in doses of 500 mg intramuscularly in 27 men (group 1) and 23 women (group 2) and 250 mg in 48 men (group 3) and 45 women (group 4) with uncomplicated urogenital gonorrhoea. Similar numbers of patients in each group were treated with 2 MIU intramuscular Bicillin (procaine penicillin 1.5 g plus benzylpenicillin 300 mg (Brocades, Weybridge, Surrey, England). Success of treatment was measured as one or two negative cultures after three or more days. The success rate for ceftriaxone was 100% in 19 evaluable men and 19 women treated with 500 mg and in 38 men and 31 women treated with 250 mg, including one infection due to penicillinase producing Neisseria gonorrhoeae (PPNG). Success rates for Bicillin were 90% (19/21) evaluable patients cured in group 1, 100% (19/19) in group 2, 95% (37/39) in group 3, and 92% (33/36) in group 4. Both drugs were well tolerated. Each isolate of N gonorrhoeae isolated was sensitive to 0.05 mg/l or less of ceftriaxone.